2001
DOI: 10.1046/j.1439-0310.2001.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in Advertisement Calls of Territorial Male Green Frogs, Rana clamitans: Implications for Individual Discrimination

Abstract: 2000: Individual variation in advertisement calls of territorial male green frogs, Rana clamitans: implications for individual discrimination. Ethology 107, 65Ð84. AbstractIndividuals of many territorial species discriminate between familiar territorial neighbors and unfamiliar strangers based on individual dierences in acoustic signals. Many anuran amphibians are territorial and use primarily acoustic communication during social interactions, but evidence for acoustically mediated individual discrimination is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
109
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 53 publications
(97 reference statements)
14
109
1
2
Order By: Relevance
“…We intentionally collected just a tiny samples of frogs as Petittt et al [5] suggested that sample size which biologically meaningful is the sample size that relevance with actual size in natural breeding aggregations. The use large sample size into analysis may overestimate the complexity of recognition problem [2]. Although M. achatina often congregate in quite a large number during breeding sessions, their distribution is not technically random over a breeding area.…”
Section: Call Recordingmentioning
confidence: 99%
See 3 more Smart Citations
“…We intentionally collected just a tiny samples of frogs as Petittt et al [5] suggested that sample size which biologically meaningful is the sample size that relevance with actual size in natural breeding aggregations. The use large sample size into analysis may overestimate the complexity of recognition problem [2]. Although M. achatina often congregate in quite a large number during breeding sessions, their distribution is not technically random over a breeding area.…”
Section: Call Recordingmentioning
confidence: 99%
“…The initial step to evaluate whether an individual could be distinguished from the others is by inspecting disparities of particular signal characters among individuals or by comparing the different levels of variability within the population. Individuality occurs in a population if the value of some characteristics exhibit greater among-individual variation than within-individual variation [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…duration, bandwidth, peak frequency) of elements that constitute the acoustic signal, or more obvious shifts in composition of elements of call repertoire (Bee et al, 2001;Ryan & Rand, 2003;Boul et al, 2007;Guerra & Ron, 2008;Rodríguez et al, 2010). Although intraspecifi c variation of discrete elements occurs to some extent among acoustic signals of sympatric males of Neotropical anurans (e.g., Guerra & Ron, 2008;, fi xed diff erences have also been reported among allopatric groups of individuals, and these diff erences have been generally attributed to evolutionary eff ects of isolation by distance or vicariance, potentially reinforced by sexual selection (Boul et al, 2007;Guerra & Ron, 2008;Amézquita et al, 2009).…”
mentioning
confidence: 99%